An introduction to methodological issues when including non‐randomised studies in systematic reviews on the effects of interventions. (24th January 2013) - Reeves, Barnaby C.; Higgins, Julian P. T.; Ramsay, Craig; Shea, Beverley; Tugwell, Peter; Wells, George A.; Reeves, Barnaby C.; Wells, George A.
<x xml:space="preserve">Abstract</x> Background Methods need to be further developed to include non‐randomised studies (NRS) in systematic reviews of the effects of health care interventions. NRS are often required to answer questions about harms and interventions for which evidence from randomised controlled trials (RCTs) is not available. Methods used to review randomised controlled trials may be inappropriate or insufficient for NRS. Aim and methods A workshop was convened to discuss relevant methodological issues. Participants were invited from important stakeholder constituencies, including methods and review groups of the Cochrane and Campbell Collaborations, the Cochrane Editorial Unit and organisations that commission reviews and make health policy decisions. The aim was to discuss methods for reviewing evidence when including NRS and to formulate methodological guidance for review authors. Workshop format The workshop was structured around four sessions on topics considered in advance to be most critical: (i) study designs and bias; (ii) confounding and meta‐analysis; (iii) selective reporting; and (iv) applicability. These sessions were scheduled between introductory and concluding sessions. Summary This is the first of six papers and provides an overview. Subsequent papers describe the discussions and conclusions from the four main sessions (papers 2 to 5) and summarise the proposed guidance into lists of issues for review authors to consider (paper 6). Copyright © 2013 John Wiley & Sons, Ltd.